REDEFINISI KEWAJIBAN BELA NEGARA BAGI GENERASI Z MELALUI LITERASI DIGITAL DAN PENANGKALAN HATE SPEECH - Rizka Amelia Putri; Meiva Widiastanti; Nasywa Hanifah Vita Putri; Neza Amelia Agustina; Valenciana Dhepa Mezzaluna; Suryo Ediyono (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
The concept of state defense (bela negara) has traditionally been associated with physical and military defense. However, in the era of information disruption, threats to national sovereignty and unity have shifted to the digital realm, such as the spread of hate speech, misinformation, and provocative narratives that threaten social integration. This study aims to redefine the meaning and obligations of national defense, particularly for Generation Z as digital natives, and to explain the strategic role of digital literacy in countering hate speech on social media. Through a qualitative approach using a literature review based on credible sources, this study explores how digital literacy has become a primary instrument of national defense today. The findings indicate that national defense for Generation Z is no longer limited to taking up arms but involves using critical thinking, digital ethics, and technological skills to counter hate speech. Proficient digital literacy enables Generation Z to become producers of positive content and active agents of change in cyberspace. This study is expected to promote the strengthening of digital citizenship through active participation in filtering information, countering hate narratives, and disseminating positive content is a tangible manifestation of the duty of national defense in the digital age. The active engagement of Generation Z in the digital era is a crucial pillar for maintaining the stability and integrity of the Unitary State of the Republic of Indonesia